Kinetic and Mechanistic Investigations of Multielectron Transfer Reactions Induced by Stored Electrons in TiO 2 Nanoparticles: A Stopped Flow Study - Mohamed, Hanan H. (2011)
The kinetics and the mechanism of various multielectron transfer reactions initiated by stored electrons in TiO2 nanoparticles have been investigated employing the stopped flow technique. Moreover, the optical properties of the stored electrons in the TiO2 nanoparticles have been studied in detail following the UV (A) photolysis of deaerated aqueous suspensions of TiO2 nanoparticles in the presence of methanol.The reduction of common electron acceptors that are often present in photocatalytic systems such asO2, H2O2, and NO3 - has been investigated. The experimental results clearly show that thestored electrons reduce O2 and H2O2 to water by multielectron transfer processes. Moreover, NO3 - is reduced via the transfer of eight electrons evincing the formation of ammonia. On the other hand, the reduction of toxic metal ions, such as Cu(II), has been studied mixing their respective anoxic aqueous solutions with those containing the electrons stored in the TiO2  particles. A twoelectron transfer is found to occur, indicating the reduction of the copper metal ion into its non toxic metallic form. Other metal ions, such as Zn(II) and Mn(II), could not be reduced by TiO2 electrons, which is readily explained on the bases of their respective redox potentials. The underlying reaction mechanisms are discussed in detail.